Strengthening Key Management Systems with Dedicated Hardware Security Modules (HSMs) - Patel, Bhushan Jayeshkumar (Journal of Research in Science and Engineering, 2026)
As cyber threats become increasingly sophisticated, organizations must implement robust security measures to protect cryptographic keys. This article explores how integrating Dedicated Hardware Security Modules (HSMs) into Key Management Systems (KMS) enhances security by providing a tamper - resistant environment. The study examines common challenges in key management, such as limited control, integration gaps, and restricted visibility, and explains how Dedicated HSMs address these concerns. Additionally, it discusses key features such as isolated partitioning, customer ownership of cryptographic roles, end - to - end encryption, and high availability. The findings highlight that Dedicated HSM solutions offer enterprises the control and security they need to safeguard cryptographic infrastructure in compliance - driven environments.